Capacidades estatais no Sistema Único de Assistência Social e suas implicações sobre a oferta dos serviços socioassistenciais - Kelly Cordeiro dos Santos (2020)
This dissertation deals with state capacities within the scope of social assistance policy, more specifically the influence of technical-administrative and political skills, bureaucratic capacity, on the offer of two social assistance services. It also incorporates an evolutionary analysis of the infrastructure and financial capacity of this policy. The theoretical discussion permeates, in addition to its own debate around each capacity, the bases of Brazilian federalism and the institutional mechanisms adopted by the federal government to induce the performance of subnational entities and encourage the development of such capacities. From this panorama, a logistic regression model is presented, which informs the increased odds ratio for carrying out comprehensive social work with families, through the socio-assistance services analyzed, in the presence of certain explanatory variables related to technical-administrative and political skills, controlled by the variables region and size of the municipality, which, as verified, present important variations in infrastructure and financial capacities. The informational bases for such analyzes come from observational data extracted from public banks, mainly from the SUAS Census.